2015
DOI: 10.3389/fpls.2015.00394
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of AtTZF1, AtTZF2, and AtTZF3 homolog gene regulation by salt stress in evolutionarily distant plant species

Abstract: Arginine-rich tandem zinc-finger proteins (RR-TZF) participate in a wide range of plant developmental processes and adaptive responses to abiotic stress, such as cold, salt, and drought. This study investigates the conservation of the genes AtTZF1-5 at the level of their sequences and expression across plant species. The genomic sequences of the two RR-TZF genes TdTZF1-A and TdTZF1-B were isolated in durum wheat and assigned to chromosomes 3A and 3B, respectively. Sequence comparisons revealed that they encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…This is congruent with earlier studies on arabidopsis carried out by different worker (Lopez-Molina et al, 2002 ; Piskurewicz et al, 2008 ). As described earlier, D'Orso et al ( 2015 ) have observed that these genes negatively regulate seed germination by delaying the process when exposed to salt stress. This could be an indicator of the role of RR-TZF encoding genes in developmental processes as well, thereby targeting genes that play integral role in seed germination, such as genes involved in ABA and GA signaling pathways.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…This is congruent with earlier studies on arabidopsis carried out by different worker (Lopez-Molina et al, 2002 ; Piskurewicz et al, 2008 ). As described earlier, D'Orso et al ( 2015 ) have observed that these genes negatively regulate seed germination by delaying the process when exposed to salt stress. This could be an indicator of the role of RR-TZF encoding genes in developmental processes as well, thereby targeting genes that play integral role in seed germination, such as genes involved in ABA and GA signaling pathways.…”
mentioning
confidence: 61%
“…Interestingly the presence of arginine rich motif in tandem zinc finger protein is a feature unique to plants (Bogamuwa and Jang, 2014 ). Extensive genomic studies have confirmed their presence in Arabidopsis thaliana, Oryza sativa, Medicago truncatula, Populas trichocarpa, Zea mays , bryophyte Physcomitrella patens , algae Chlamydomonus reinhardtii , and more recently in durum wheat (Wang et al, 2008 ; Chai et al, 2012 ; Peng et al, 2012 ; Zhang et al, 2013 ; D'Orso et al, 2015 ). Expression level analyses have revealed their involvement in multiple tissue specific developmental processes as well as other regulatory activities.…”
mentioning
confidence: 93%
See 3 more Smart Citations